Situational Awareness towards Enhancing the Quality of Life for Rural Women in Some Villages in Zefta Center, Gharbia Governorate - Elserafy, Rabab Selim (Journal of Humanities & Social Sciences, 2023)
The research aimed to identify the level of situation awareness towards enhancing the quality of life for rural women, by constructing a scale and detecting its factor structure using confirmatory factor analysis, and verifying its reliability and validity, then applying it. The research was conducted in Gharbia Governorate, at three randomly selected villages from Zefta center were chosen; Al-Ghareeb, Nahatai, and Sennar El-Kubra, with a total sample size of 366 participants, randomly selected, and data were collected using a personal interview questionnaire. The research findings indicated: 1- The scale of situation awareness towards enhancing the quality of life for rural women has satisfactory psychometric properties, and it consists of five dimensions; personal quality of life, family quality of life, social quality of life, economic quality of life, and environmental quality, with personal quality of life. The latter dimension is consisting of three sub-dimensions; namely physical health quality, mental health quality, and psychological health quality. 2- The level of situation awareness towards enhancing the quality of life for rural women was moderate in all dimensions, including the total quality of life, personal quality of life, social quality of life, and environmental quality, with percentages of (83.30%, 62.60%, 42.35%, and 48.60%) respectively. However, the level of situation awareness towards enhancing the family quality of life and economic quality of life was high, with percentages of (66.67% and 60.11%) respectively.